Answer:
14x-12
Step-by-step explanation:
Simplify (2x-3)(7x+4).
Expand the brackets. Remember brackets mean to multiply.
We multiply the 2x and the 7x to get 14x and we multiply the -3 by 4 to get -12 as shown below;
(2x-3)(7x+4)
14x-12
Answer:
the answer is 3
Step-by-step explanation:
Answer:
117
u welcome
Step-by-step explanation:
Answer:
y =
x
Step-by-step explanation:
slope-intercept form: y = mx + b
Given: slope(m) =
, point (4, -3)
We already have the value of m, but we need to find the value of b. To do this, input the given values of the slope and the point into the equation:
-3 =
(4) + b
Solve for b:
-3 =
(4) + b
-3 = -3 + b
0 = b
The value of b is zero. We can now write the equation:
y =
x + 0
y =
x
The equation written in slope-intercept form is: y =
x
Answer:
I did this its A
Step-by-step explanation: